A mimetic of the mSin3-binding helix of NRSF/REST ameliorates abnormal pain behavior in chronic pain models. Issue 20 (15th October 2017) - Ueda, Hiroshi; Kurita, Jun-ichi; Neyama, Hiroyuki; Hirao, Yuuka; Kouji, Hiroyuki; Mishina, Tadashi; Kasai, Masaji; Nakano, Hirofumi; Yoshimori, Atsushi; Nishimura, Yoshifumi
Graphical abstract: Highlights: Dysregulation of the neural repressor, NRSF is related to neuropathic pain. Based on the structure of NRSF bound to mSin3, mS-11 was designed and synthesized. NMR shows that the mS-11binding site on mSin3 is similar to that of NRSF. mS-11 reverses hyposensitivity of the peripheral C-fiber response in neuropathy. mS-11 reverses hypersensitivity of hyperalgesia/allodynia in a fibromyalgia model. Abstract: The neuron-restrictive silencing factor NRSF/REST binds to neuron-restrictive silencing elements in neuronal genes and recruits corepressors such as mSin3 to inhibit epigenetically neuronal gene expression. Because dysregulation of NRSF/REST is related to neuropathic pain, here, we have designed compounds to target neuropathic pain based on the mSin3-binding helix structure of NRSF/REST and examined their ability to bind to mSin3 by NMR. One compound, mS-11, binds strongly to mSin3 with a binding mode similar to that of NRSF/REST. In a mouse model of neuropathic pain, mS-11 was found to ameliorate abnormal pain behavior and to reverse lost peripheral morphine analgesia. Furthermore, even in the less well epigenetically defined case of fibromyalgia, mS-11 ameliorated symptoms in a mouse model, suggesting that fibromyalgia is related to the dysfunction of NRSF/REST. Taken together, these findings show that the chemically optimized mimetic mS-11 can inhibit mSin3-NRSF/REST binding and successfully reverse lost peripheral and central morphine analgesia in mouse models of pain.